2011
DOI: 10.1161/hypertensionaha.110.163600
|View full text |Cite
|
Sign up to set email alerts
|

Pathways Leading to Atherosclerosis

Abstract: Abstract-Several risk factors of cardiovascular diseases have been studied using direct association measures. Because the incidence of obesity and cardiovascular diseases is rising, it is important to correctly model these risk factors involved in development of cardiovascular diseases. Until now, statistical methods lacked to achieve this goal because of complex interrelationships involved. Structural Equation Modeling (SEM) is an advanced statistical technique that enables solving this issue. The aims of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…To facilitate convergence, BMI was treated as continuous because the underweight category contained relatively few participants. To reduce multicollinearity between systolic/diastolic blood pressure, the worst (higher) z score for each measure was retained (33). The effects are decomposed into indirect (mediating) effects, which are summed to provide the total indirect effect (32).…”
Section: Resultsmentioning
confidence: 99%
“…To facilitate convergence, BMI was treated as continuous because the underweight category contained relatively few participants. To reduce multicollinearity between systolic/diastolic blood pressure, the worst (higher) z score for each measure was retained (33). The effects are decomposed into indirect (mediating) effects, which are summed to provide the total indirect effect (32).…”
Section: Resultsmentioning
confidence: 99%
“…However, our results support the previous findings in adults showing only indirect effect of fat mass on cIMT using advanced statistical approaches. (11) Finally, our sample was enriched with minorities with T2DM and therefore may provide results that are not generalizable to other populations.…”
Section: Discussionmentioning
confidence: 98%
“…Structural equation models based on previous findings (11, 12) and theoretical rationales were tested to examine the relationships among CV risk factors (figure 1). Structural equation modeling allows measurement models and latent variables as a feature, where an outcome or factor could not be measured directly but though multiple indicators.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, we measured fat and lean mass weight and found significantly decreased fat mass in mice administered C. lanatus `sentinel' extract. Increased fat mass contributes to enhanced risk for developing atherosclerosis [24,25]. Despite lack of direct evidence, it is possible that supplementation of C. lanatus `sentinel' extract may be beneficial for protecting against atherosclerosis by reducing fat mass.…”
Section: Discussionmentioning
confidence: 99%